The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/microorganisms10112252
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characterization of Antimicrobial Resistant Pathogens in a Pig Farm, Slaughterhouse, Meat Processing Plant, and in Retail Stores

Abstract: The emergence of antibiotic resistance in foodborne pathogens isolated from meat pro-ducts and their producing environment has been an increasing and leading threat to public health. The aim of the study was to identify pathogens and their antimicrobial resistance isolated from pig production to pork meat distribution phases. Through this study, food spoilage and foodborne or clinical pathogenic bacteria were isolated and identified from pork (belly and neck) meat product and its related environmental samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Understanding the risk factors associated with different microorganisms has led to improvements in controlling microbial contamination [ 1 , 2 ]. This Special Issue was established to gather and share high-quality scientific articles on microbial contamination and contains six original research articles covering a range of diverse topics related to microbial contamination [ 3 , 4 , 5 , 6 , 7 , 8 ]. As revealed from the retrospective analysis of the articles, microbial contamination challenges are often focused around three key issues—the detection, genophenotypic characterization, and antimicrobial resistance (AMR) of microbial contaminants, whereby all of which are interconnected in a pleiotropic and epistatic manner.…”
Section: Detection and Identification Of Microbial Contaminantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding the risk factors associated with different microorganisms has led to improvements in controlling microbial contamination [ 1 , 2 ]. This Special Issue was established to gather and share high-quality scientific articles on microbial contamination and contains six original research articles covering a range of diverse topics related to microbial contamination [ 3 , 4 , 5 , 6 , 7 , 8 ]. As revealed from the retrospective analysis of the articles, microbial contamination challenges are often focused around three key issues—the detection, genophenotypic characterization, and antimicrobial resistance (AMR) of microbial contaminants, whereby all of which are interconnected in a pleiotropic and epistatic manner.…”
Section: Detection and Identification Of Microbial Contaminantsmentioning
confidence: 99%
“…Detecting microbial contaminants in samples with low biomass and complex matrices is a challenging task that requires rapid, sensitive, and accurate detection methods for effective safety interventions. In this Special Issue, several articles explore ways to overcome these challenges and improve microbial detection outcomes [ 3 , 4 , 5 , 6 , 8 ].…”
Section: Detection and Identification Of Microbial Contaminantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Bae et al (8) reported the first study tracking foodborne pathogens in pigs and related pork products at all points along the pork supply chain, including farms, slaughterhouses, meat processing plants, and retail stores, in Korea. In particular, Y. enterocolitica and Shiga toxin-producing E. coli were the major pathogens isolated from carcasses in slaughterhouses.…”
mentioning
confidence: 99%